2019
DOI: 10.1371/journal.pmed.1002822
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rapid HIV treatment initiation after national “treat all” policy adoption in 6 sub-Saharan African countries: Regression discontinuity analysis

Abstract: BackgroundMost countries have formally adopted the World Health Organization's 2015 recommendation of universal HIV treatment ("treat all"). However, there are few rigorous assessments of the real-world impact of treat all policies on antiretroviral treatment (ART) uptake across different contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 26 publications
4
56
1
2
Order By: Relevance
“…Importantly, this was a secondary data analysis of studies conducted in 2013 or earlier and the prevalence and characteristics of people with advanced HIV may have changed. Nevertheless, although most countries have adopted 'treat all' there may be delays in implementation at the level of all facilities and our results would thus remain relevant for settings where 'treat all' has not yet been fully implemented [29]. Finally, as stated in the methods, the surveys were not representative at country level and subgroup analysis was not planned at the design stage analysis, therefore, our results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, this was a secondary data analysis of studies conducted in 2013 or earlier and the prevalence and characteristics of people with advanced HIV may have changed. Nevertheless, although most countries have adopted 'treat all' there may be delays in implementation at the level of all facilities and our results would thus remain relevant for settings where 'treat all' has not yet been fully implemented [29]. Finally, as stated in the methods, the surveys were not representative at country level and subgroup analysis was not planned at the design stage analysis, therefore, our results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 84%
“…To date, studies on whether HIV "Treat All" has improved ART initiation among adolescents are inconclusive. Positive effects have been shown in some studies, while others have shown that they are still at risk of not initiating ART [23,[27][28][29]. To our knowledge, no evidence-based strategies are currently being implemented in Zimbabwe on a broader scale under "Treat All" to promote ART initiation among adolescents and young adults.…”
Section: Plos Onementioning
confidence: 99%
“…19 The MOH has also become a leader in progressive antiretroviral therapy programmes, such as Option B+ and universal treatment. [20][21][22] Given this ongoing success in treating chronic infectious disease as well as the resources invested in these programmes, and Malawi's growing burden of chronic NCDs, integrated care for chronic diseases is an attractive solution. Applying lessons from HIV care delivery to NCDs is well described, and an integrated approach is increasingly recognised as a possible delivery model, particularly for primary care, with much of the literature focused on calling for various integrated approaches.…”
Section: Introductionmentioning
confidence: 99%